Nematode prevalence, helminth management practices and anthelmintic resistance in small ruminants in the Mid-Rift Valley of Ethiopia - Boomker, Jacob Diederik Frederik (University of Pretoria, 2013)
Thesis (PhD (Veterinary Science))--University of Pretoria, 2005.